The present situation of freshwater crayfish, Astacus leptodactylus (Eschscholtz, 1823) in Turkey - Harlioglu, MM (Elsevier Science Bv, 2004)
The only native crayfish species in Turkey, Astacus leptodactylus, is widely distributed in lakes and ponds in many parts of the country. Its distribution area was considerably expanded in Turkey after 1985 because of its commercial importance and declined catches from traditional good fisheries. Although consumption of A. leptodactylus has always been very low in Turkey, it was exported to western Europe until 1986. Due to over-fishing, pollution and a disease (crayfish plague), the total production decreased dramatically to 200 from 5000 tonnes annually. In recent years (1991-1998), there has been a gradual increase in the production of crayfish in Turkey from 320 to 1500 tonnes, but plague is still present. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Astacus leptodactylus; crayfish; harvest; Turkey